Assessing the effectiveness of internal Sharıʿah audit structure and its practices in Islamic financial institutions: a case study of Islamic banks in Yemen - Algabry, Latifah; Syed Jaafar Alhabshi, Syed Musa; Soualhi, Younes; Othman, Anwar Hasan Abdullah (Emerald Publishing Limited, 2020)
Purpose – This study aims to explore and assess the key Sharıʿah governance factors that may have an influence on the internal Sharıʿah audit structure and its practices in Islamic financial Institutions in Yemen, particularly in the Islamic banking sector. Design/methodology/approach – To do so, the study adopts a qualitative approach employing case study analysis, and both primary and secondary data are used to formulate the appropriate interview questions and achieve the objectives of the study. Findings –The authors observed that the key factors that help in assessing the internal Sharıʿah audit structure and its practices are Sharıʿah auditor charter, audit plan and audit manual. In addition, the authors observed that, in general, internal Sharıʿah audit tends to be subjective in Yemeni banks because they depend on the internal Sharıʿah auditor’s qualifications and experience more than formal guidelines and regulations. This is because there are no detailed internal Sharıʿah audit plans or detailed audit manual. Moreover, the internal Sharıʿah auditor charter is not comprehensive in explaining the duties required of the internal Sharıʿah auditor, and it is mixed with the Sharıʿah Supervisory Board (SSB) duties. This means the internal Sharıʿah auditor lacks the critical tools that enable him to achieve the desired audit manual objectives where the effectiveness of internal Sharıʿah audit can be measured. Practical implications – One of the important implications of this study is providing very important guidance about enhancing the areas where shortfalls are found within the Sharıʿah governance process in the Yemeni banking system. This enhancement process of the internal factors of Sharıʿah governance can be achieved by increasing the awareness of the enhancing internal Sharıʿah audit structure as it reflects ultimately on the internal Sharıʿah auditor’s role and his practices. Originality/value – Understanding the effectiveness of internal Sharıʿah audit structure among internal auditors will improve the Sharıʿah audit framework standards, enhance the Sharıʿah knowledge among internal auditors and provide general guidelines to design audit programmes for Sharıʿah governance auditing process